(3MeGSI CHj JeGes - (3CHh JeGe GdWGFj , CHh JeGe MHjH Hf ChS Hf GdMGQK GdWGFj,J (B231 (3g` s
(3ChdgG (B:s
(3eHJhQ hChd GdehLhO efgG bhdg(B: (3CNTi aXGYI Ye Ch LaGA CN hcfJ CHbi YdjgG ef CPi Gdcde s
(3BNQgG (B:s
(3eHJhQ cPd, hBNQ GdehLhO efgG bhdg(B: (3CHJ GdQhGOa hGdKOi dbeUgG eS GdHWhf hCf JeS XghQG hEPG GdQjGM eY GdYTi JfGhMJ fHgf MGSOI hgLf ZjhQG s
(3bWYI ef fSNI KGefIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B170s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B273 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B691s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI HZOGO (B- (3eYgO GdOQGSGJ GdESdGejI GdYdjG (B(390) s
Keywords: (3GdCOHs